ANALISIS TINGKAT PERTUMBUHAN LALU LINTAS BERDASARKAN NILAI LHR PADA RUAS JALAN JENDERAL SUDIRMAN DI KOTA PALEMBANG - Rusdani, Muhammad Lutfhi; Wahab, Wahyuni (Ensiklopedia of Journal, 2024)
The effect of congestion causes the creation of a condition of traffic congestion or cessation due to the number of vehicles that are too many and exceed the available road capacity. Based on Average Daily Traffic (LHR) data from the South Sumatra National Road Implementation Center (BBPJN SUMSEL) on the Sudirman Km 0 - Km 5 General Road section, it shows that the average daily traffic volume value has increased from 2019 to 2023. The purpose of this study was to analyze the value of traffic growth and estimates of future traffic volume. The results of this study are the traffic growth value on the Sudirman road section based on the average daily traffic volume using four methods for grouping vehicles based on the types of MC, LV and HV and the traffic growth value on the Sudirman road section based on daily traffic volume is MC = 4.87% LV = 1.26% HV = 12.38%, for Total Vehicles / day 5.71% and 4.55% for Total Vehicles in Smp/day.    Keywords: Traffic Growth Rate, LHR Value, Congestion.